2010
DOI: 10.1097/sla.0b013e3181fd37e8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of 68Ga-DOTATOC Positron Emission Tomography/Computed Tomography on the Multimodal Management of Patients With Neuroendocrine Tumors

Abstract: In this study, 68Ga-DOTATOC PET/CT proved clearly superior to CT and/or MRI for detection and staging of NET. More important, 68Ga-DOTATOC PET/CT impacted our treatment decision in more than every second patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
129
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(135 citation statements)
references
References 21 publications
3
129
0
3
Order By: Relevance
“…Thus, additional evidence of metastatic lesions was evident in O30%, particularly when localized within the skeletal system (Buchmann et al 2007), and localization of unknown primary NENs was established in 39% of cases (Prasad et al 2010). The superiority of 68 Ga-DOTA-based PET/CT over anatomic imaging using CT or MRI and its impact on treatment were demonstrated in a recent study on 52 NEN patients who underwent both standard morphological imaging and 68 Ga-DOTATOC PET/CT (Frilling et al 2010). The primary treatment decision, based solely on CT and/or MRI results, was altered in 59.6% of patients when 68 Ga-DOTATOC PET/CT results were considered.…”
Section: R166mentioning
confidence: 99%
“…Thus, additional evidence of metastatic lesions was evident in O30%, particularly when localized within the skeletal system (Buchmann et al 2007), and localization of unknown primary NENs was established in 39% of cases (Prasad et al 2010). The superiority of 68 Ga-DOTA-based PET/CT over anatomic imaging using CT or MRI and its impact on treatment were demonstrated in a recent study on 52 NEN patients who underwent both standard morphological imaging and 68 Ga-DOTATOC PET/CT (Frilling et al 2010). The primary treatment decision, based solely on CT and/or MRI results, was altered in 59.6% of patients when 68 Ga-DOTATOC PET/CT results were considered.…”
Section: R166mentioning
confidence: 99%
“…Similarly, NETs are another subset of tumors that demonstrate this phenomenon of tumor heterogeneity. [ DOTA-TOC uptake) and an associated significant increase in glycolytic metabolism (leading to increased FDG uptake) [17][18][19][20][21]. Again, high FDG avidity in the tumors is usually associated with a worse patient prognosis [22,23].…”
Section: Classification and Clinical Examples Of Tumor Heterogeneity mentioning
confidence: 99%
“…The superiority of 68 Ga-labeled somatostatin analogs in terms of specificity, sensitivity, staging accuracy, detection rate, quantification, and acquisition time over 18 F-FDG (5), 18 F-3,4-dihydroxyphenylalanine (6), 123 Imetaiodobenzylguanidine (7,8), 111 In-DTPA-pentetreotide (9), 18 F-NaF, and 99m Tc-dicarboxypropanediphosphonate (10) has been demonstrated. The high impact of 68 Ga PET/CT on patient management can be illustrated by the fact that the course of treatments was changed or adjusted in 50%-60% of cases on the basis of 68 Ga PET/CT results (11)(12)(13)(14)(15). Thorough analysis of the publications on 16 clinical studies involving 567 patients with suspected thoracic or gastroenteropancreatic NETs suggested PET/CT with 68 Galabeled somatostatin analogs as an independent first-line diagnostic imaging method for this category of patients (16).…”
mentioning
confidence: 99%